2017
DOI: 10.1016/j.joca.2016.10.011
|View full text |Cite
|
Sign up to set email alerts
|

Controlling joint instability delays the degeneration of articular cartilage in a rat model

Abstract: Re-stabilization of joint instability may suppress inflammatory cytokines, thereby delaying the progression of OA. Joint instability is a substantial contributor to cartilage degeneration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
62
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(69 citation statements)
references
References 40 publications
7
62
0
Order By: Relevance
“…In order to verify the protective effect of EAF from SSG on OA development, in the present study, we evaluated the in vivo antiosteoarthritic effect of intra-articular administration of EAF from SSG on a classical rat OA model surgically induced by ACLT. This OA animal model is characterized by joint instability, intra-articular inflammation and structural joint changes, which are similar to typical osteoarthritic features observed in human OA [7,8]. Our findings would be helpful to uncover the modern pharmacological aspects of SSG, and lay the experimental foundation for the better clinical application or food therapy of SSG for OA control.…”
Section: Introductionsupporting
confidence: 56%
See 1 more Smart Citation
“…In order to verify the protective effect of EAF from SSG on OA development, in the present study, we evaluated the in vivo antiosteoarthritic effect of intra-articular administration of EAF from SSG on a classical rat OA model surgically induced by ACLT. This OA animal model is characterized by joint instability, intra-articular inflammation and structural joint changes, which are similar to typical osteoarthritic features observed in human OA [7,8]. Our findings would be helpful to uncover the modern pharmacological aspects of SSG, and lay the experimental foundation for the better clinical application or food therapy of SSG for OA control.…”
Section: Introductionsupporting
confidence: 56%
“…After a 1-week acclimation period, all animals were randomly divided into 3 groups of 12 rats in each group: (1) shamoperated control group; (2) ACLT OA model control group; (3) ACLT+ intra-articular administation of EAF from SSG group. The anterior cruciate ligaments in the right knees of rats in 2 and 3 groups were surgically transected as previously described [7][8][9] to establish OA model. Arthrotomy without anterior cruciate ligament damage was performed in sham-operated rats.…”
Section: Animals and Groupsmentioning
confidence: 99%
“…These previous studies pointed out that it is important to move articulation closer to normal and move it for protecting from early phase after injury. In addition, previous studies have shown that controlling abnormal joint movement in a completely ruptured ACL results in the down-regulation of inflammatory responses [ 33 ] and leads to spontaneous healing [ 27 ]. Furthermore, importance of weight-bearing has been pointed out in previous study [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Prior research showed that changing the joint kinematics of a knee with complete ruptured ACL results in the down-regulation of inflammatory responses [ 33 ] and leads to spontaneous healing [ 27 ]. These previous studies used the CAM model used for the purpose of controlling abnormal knee joint movement without restricted knee flexion (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…This procedure was adapted from Murata et al . Both hindlimbs were harvested at 4 weeks postsurgery.…”
Section: Methodsmentioning
confidence: 99%